Pengembangan Bahan Ajar BIPA pada Keterampilan Menulis Cerpen Tingkat Dasar Bermuatan Budaya Indonesia dengan Media Audiovisual - Sintia, Haqsir Venny; Muliastuti, Liliana; Eriyani, Reni Nur (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This article discusses the application of teaching materials to a BIPA (Indonesian Language for Foreign Speakers) teaching, especially in reading skills through a culturally charged audiovisual learning medium. The purpose of this study was to explain teaching materials delivered in culturally charged audiovisual media at the basic level of BIPA teaching with short story writing skills. Audiovisual media pages also accommodate the needs of online BIPA learning. This audiovisual media can be in the form of dialogue videos and explanation videos, as well as supporting media in the form of materials or handbooks. The research method used is descriptive qualitative. The reference source used here is in the form of the BIPA AI guidebook